Pengembangan Model Mobile Learning Berbasis Aplikasi Android pada Mata Kuliah Sejarah ASEAN - Adhitya Rol Asmi; Aulia Novemy Dhita Surbhakti; Y. Yunani; S. Syarifuddin (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2019)
This research is entitled "Development of an Android Application-Based Mobile Learning Model in the History of ASEAN Countries" in the Sriwijaya University Historical Education Study Program. This research is a type of development research that uses the development model of Dick and Carey. The purpose of this study is to develop a Mobile Learning model based on Android applications in lectures on Southeast Asian history that are valid and have an effect on effectiveness. Observation and questionnaire data show the use of the SEA-Hole Mobile Learning application (South East Asian Historic Mobile Learning) has a good impact in supporting the Southeast Asian History lecture process, such as making it easier to understand Southeast Asian History lecture material because it is supported by images and videos. Some entries from Experts and small groups are used to produce a valid application prototype. Overall the SEA-Hole Mobile Learning application has a good effect to be used as a support for mobile lectures.